(2m + 3)(m^2 - 2m + 1) =
2m(m^2 - 2m + 1) + 3(m^2 - 2m + 1) =
2m^3 - 4m^2 + 2m + 3m^2 - 6m + 3 =
2m^3 -m^2 - 4m + 3 <===
Answer:
3
Step-by-step explanation:
YS = DI = 6
A = YS * AI = 24
height = A/b = 24 / 8 = 3
Answer: 2.5 or 2 1/2.
Step-by-step explanation:
Answer:
33+12t−21t^2
Step-by-step explanation:
(2t-7)²-(5t-4)²
Use binomial theorem (a−b)^2 = a^2−2ab+b^2 to expand (2t-7)².
4t^2−28t+49−(5t-4)²
Use binomial theorem (a−b)^2 = a^2−2ab+b^2 to expand (5t-4)².
4t^2−28t+49−(25t^2−40t+16)
To find the opposite of 25t^2
−40t+16, find the opposite of each term.
4t^2−28t+49−25t^2−40t+16
Combine 4t^2 and −25t^2 to get −21t^2.
−21t^2−28t+49+40t−16
Combine −28t and 40t to get 12t.
−21t^2+12t+49−16
Subtract 16 from 49 to get 33.
−21t^2+12t+33
Swap terms to the left side.
33+12t−21t^2
I hope this helped!
Answer:
The price of hot dog is $2.5 and that of a pretzel is $1.25.
Step-by-step explanation:
Let the cost of hotdogs be x and that of pretzels be x.
So,
4x+3y = 13.75 ...(1)
and
2x+5y = 11.25 ...(2)
Multiply equation (2) by 2.
4x+10y = 22.5 ...(3)
Subtract equation (1) from (3).
4x+10y-(4x+3y) = 22.5-13.75
4x+10y-4x-3y = 8.75
7y = 8.75
y = 1.25
Put the value of y in equation (1).
4x+3(1.25) = 13.75
4x+3.75 = 13.75
4x = 13.75-3.75
4x = 10
x = 2.5
So, the price of hot dog is $2.5 and that of a pretzel is $1.25.